2009
DOI: 10.4102/sajhrm.v6i3.145
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Leadership, Job satisfaction and Organisational Commitment

Abstract: The aim of this study was to investigate the relationship between leader empowerment behaviour, job satisfaction and organisational commitment for employees in selected organisations in South Africa. A cross-sectional survey design with a random sample (N = 209) was used. The Leader Empowering Behaviour Questionnaire (LEBQ), Revised Minnesota Satisfaction Questionnaire (MSQ) and Organisational Commitment Questionnaire (OCQ) were administered. The scales showed acceptable internal consistencies. Statistically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 38 publications
4
24
0
1
Order By: Relevance
“…[12,13] It is also identified with psychological well-being dissensions, brings down levels of employment fulfillment, and contribution, diminished trust and engagement and increased intention to leave. [15][16][17] 1.2 Problem statement and significance of the study Nurses' work has been viewed as a very distressing work since they need to give additional time and effort and managerial concern. [18] Employees who demonstrate separation or disengagement in work, their work practices and performance turn out to be low and they don't demonstrate any exertion or perform well.…”
Section: Psychological Empowermentmentioning
confidence: 99%
See 1 more Smart Citation
“…[12,13] It is also identified with psychological well-being dissensions, brings down levels of employment fulfillment, and contribution, diminished trust and engagement and increased intention to leave. [15][16][17] 1.2 Problem statement and significance of the study Nurses' work has been viewed as a very distressing work since they need to give additional time and effort and managerial concern. [18] Employees who demonstrate separation or disengagement in work, their work practices and performance turn out to be low and they don't demonstrate any exertion or perform well.…”
Section: Psychological Empowermentmentioning
confidence: 99%
“…[4] On the other hand, the experience of being empowered has been proposed to be an arbiter between managerial practices and the outcomes anticipated from empowered workers, such as engagement, organizational commitment, and job performance. [7,17] In addition, despite the fact that a past research directed by De Cuyper et al (2008) demonstrated that job insecurity related to work engagement, yet, a paucity of researches were available regarding nurses' psychological empowerment and its connection to work engagement and job insecurity. [19] Little is known whether nurses' perception of psychological empowerment, work engagement is related to their perception of job insecurity [19] particularly with regards to the context of Egyptian hospitals.…”
Section: Psychological Empowermentmentioning
confidence: 99%
“…These four determinants can also be regarded as psychological conditions that lead to employee engagement. The experience of being empowered has been proposed to be a mediator between empowering managerial practices and the outcomes expected from empowered workers, such as engagement, organisational commitment and job performance (Spreitzer, 1995;Stander & Rothmann, 2008). However, no studies have been found that focus on the relationship between psychological empowerment and employee engagement.…”
Section: Introductionmentioning
confidence: 97%
“…Konczak et al (2000) found significant correlations between the dimensions of the LEBQ and job satisfaction (ranging from 0.32 with accountability to 0.63 for delegation of authority). These significant correlations were also found between leader empowering behavior and intrinsic ( r = 0.64) and extrinsic ( r = 0.81) job satisfaction (Stander and Rothmann, 2009).…”
Section: Introductionmentioning
confidence: 80%